Indonesian indirect request strategies used in academic sphere: a study in Vocational Program of Universitas Brawijaya - Asih Zunaidah (Jurnal Linguistik Terapan, 2016)
People change their method of communication or use of language based on distinctive spheres, contexts and situations. Accordingly, people will not simply talk or write without even having one goal in mind. To accomplish the purpose in a systematic way, people use communicative acts or in other words, speech act. This article focuses on one type of speech act called request which is included in directive category. This study employs mixed methods of qualitative and descriptive quantitative approach using case study design. In this research, the researcher conducted a survey using questionnaires called DCT (Discourse Completion Test). The statistics obtained from the questionnaires were used to support the qualitative analysis. The result revealed that the most frequently used strategy is indirect request. Based on the analysis, the participants took social distance, relative power and the degree of imposition into account when they were making the requests in academic sphere, hence the choice of indirect strategy.